2005
DOI: 10.1016/j.ejcts.2005.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Immediate ischemic preconditioning based on somatosensory evoked potentials seems to prevent spinal cord injury following descending thoracic aorta cross-clamping

Abstract: Objective: Delayed ischemic preconditioning has demonstrated neuroprotective effects in spinal cord ischemia. We investigated the effects of immediate ischemic preconditioning based on somatosensory evoked potentials monitoring in a model of spinal cord injury due descending thoracic aorta occlusion in dogs. Methods: Twenty-one dogs were submitted to spinal cord ischemia induced by descending thoracic aorta crossclamping for 45 min. Control group underwent only the aortic cross-clamping (nZ7), group A underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…14 Mildly, oxidant-challenged cells increase their viability through complex adaptations, that result in maintained physiological functions that induce adaptations in normal cell populations. 15 The strong tendency of lower FR concentrations suggests a preconditioning effect of exercise vs H 2 O 2 . 1 N-tert butyl-a-phenyl nitrone is reported to have multiple pharmacological activities to reduce ROS, including the ability to trap alkoxyl radicals, superoxide radicals and hydroxyl radicals and to decrease inducible cytochrome (cyclooxygenase-2), as well as to inhibit nuclear factor-kB transduction.…”
Section: Discussionmentioning
confidence: 99%
“…14 Mildly, oxidant-challenged cells increase their viability through complex adaptations, that result in maintained physiological functions that induce adaptations in normal cell populations. 15 The strong tendency of lower FR concentrations suggests a preconditioning effect of exercise vs H 2 O 2 . 1 N-tert butyl-a-phenyl nitrone is reported to have multiple pharmacological activities to reduce ROS, including the ability to trap alkoxyl radicals, superoxide radicals and hydroxyl radicals and to decrease inducible cytochrome (cyclooxygenase-2), as well as to inhibit nuclear factor-kB transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Hart et al Cizkova et al 2004) showed a robust induction of HSPs with 6 and 12 min of spinal cord ischemia in a microarray analysis. Contreras (Contreras et al 2005) demonstrated spinal cord protection using immediate ischemic pre-conditioning guided by SSEP measurements but did not measure HSPs as a part of this study. Robinson et al (2005) showed an increase in HSP70 in response to ischemia in motoneurons, which reduced damage.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the preconditioning itself would induce no harm to the tissues, since the results in the IPC group were not significantly different from the results in group C, an observation similar to that observed by Iliodromitis et al 20 Another possible explanation for the absence of neuroprotection in the IPC group of our study is that the reperfusion interval between IPC and the subsequent ischemic event was only three minutes, much shorter than that of the other "protective" IPC protocols. 18,22 Recently, Contreras et al 23 demonstrated the importance of the reperfusion interval by monitoring the somatosensory evoked potentials. Further experiments using different cycles and durations of IPC and reperfusion interval are required to address the observed between-study variances.…”
Section: Discussionmentioning
confidence: 99%